Analisis Pengaruh Harga Dan Kualitas Terhadap Kepuasan Konsumen Dalam Membeli Ikan Di Pasar Wuring - Marianus Noralarai; Yoseph D. Purnama Rangga; Pipiet Niken Aurelia (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Companies that fail to satisfy their services will face complex problems. Generally, consumers who are dissatisfied will convey their bad experiences to other people and you can imagine how big the losses are from failure to satisfy customers. Therefore, every service company is obliged to plan, organize, implement and control a quality system in such a way that the service can satisfy its customers. Consumer satisfaction is influenced by the quality of service where there are five dimensions. According to Agustyn (2021), it shows that customer perceptions of service quality include perceptions related to physical facilities (Tangibles), reliability (Reliability), responsiveness (Responsiveness), guarantee (Assurance) and empathy (Empathy).